Hakikat Ilmu Pengetahuan dalam Perspektif Filsafat Pendidikan Islam - Dwi Meutia Hasni; Usiono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
As an inseparable part of Islamic civilization, the nature of science reflects a series of philosophical concepts, such as dichotomy of science, Islamization of science, integration of science, and interconnection of science. The dichotomy of science raises problems related to the sharp gap between religious science and worldly science, requiring a careful approach to overcome this disparity. Meanwhile, the Islamization of science challenges to align Islamic values with modern science, while the integration of science emphasizes the formation of a holistic framework that covers the entire spectrum of science. This article uses a literature study method, by the author tracing the literature in libraries, books, scriptures, journals, newspapers, magazines, articles, and others, most of which are found in the last five years. The results of this writing find that overall, the implications of this problem show that the development of Islamic education requires a profound transformation in the educational paradigm, improving the quality of human resources, and forming an inclusive and holistic educational vision. Only by overcoming these problems, Islamic education can play a more effective role in forming individuals who are not only superior in science, but also have a strong moral and spiritual foundation in accordance with Islamic principles.